2013
DOI: 10.1167/iovs.13-11978
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Mediated Transscleral Delivery of Macromolecules to the Posterior Segment of Rabbit Eye In Vivo

Abstract: Low-frequency ultrasound significantly enhanced the penetration of macromolecules via transscleral route. No undesirable side effects have been found for up to 2 weeks after ultrasound application. The study supports that sonication is a potentially safe and effective method to modulate transscleral barriers for delivering macromolecular therapeutics to posterior segment of the eye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…Most of the experiments were performed either in vitro on isolated cornea or sclera or ex vivo on entire excised eyes until 2006 [6]. Between 2006 and 2013, the majority of the studies were conducted in vivo [6,7,[66][67][68]. In the last in vivo study to date which has been found, dexamethasone (a steroidal anti-inflammatory agent) has been delivered to the aqueous humor at 2.8 times the passive penetration using 5-minute continuous wave ultrasound (CWUS) with moderate intensities (0.8W/cm²) at 400kHz [69].…”
Section: Efficacymentioning
confidence: 99%
See 3 more Smart Citations
“…Most of the experiments were performed either in vitro on isolated cornea or sclera or ex vivo on entire excised eyes until 2006 [6]. Between 2006 and 2013, the majority of the studies were conducted in vivo [6,7,[66][67][68]. In the last in vivo study to date which has been found, dexamethasone (a steroidal anti-inflammatory agent) has been delivered to the aqueous humor at 2.8 times the passive penetration using 5-minute continuous wave ultrasound (CWUS) with moderate intensities (0.8W/cm²) at 400kHz [69].…”
Section: Efficacymentioning
confidence: 99%
“…In the last in vivo study to date which has been found, dexamethasone (a steroidal anti-inflammatory agent) has been delivered to the aqueous humor at 2.8 times the passive penetration using 5-minute continuous wave ultrasound (CWUS) with moderate intensities (0.8W/cm²) at 400kHz [69]. In an earlier study, transscleral delivery of fluorescein-labelled dextran has been achieved using low-frequency US (40kHz) [68]. In this particular study, significant amounts of dextran were measured in the vitreous humor (up to 1.48 µg/g), while it was undetectable without applying ultrasound.…”
Section: Efficacymentioning
confidence: 99%
See 2 more Smart Citations
“…Drug delivery using sonophoresis (or ultrasound) to increase ocular tissue permeability is earlier in development and has not yet been demonstrated in clinical studies. Delivery of steroids, antibiotics, and, most recently, a large molecular weight dextran has been demonstrated in preclinical models, however [157, 160, 161]. …”
Section: Ophthalmic Drug Deliverymentioning
confidence: 99%